Respostas

2014-05-07T00:20:02-03:00
a= (-2,3,5)
b=(4,6-6)
c=(-3,-2,-1)

 v= 2ab-6ac-3bc.

primeiro vamos descobrir o valor de 
ab ; ac; bc

o vetor ab = B-A (sempre fazendo x com x ..y com y....z com z
AB = (4;6;-6)-(-2;3;5)\\\\AB=(4-(-2));(6-3);(-6-5)\\\\AB=(6;3;-11)

Vetor ac = C-A
AC=(-3;-2;-1)-(-2;3;5)\\\\\ AC=(-3-(-2));(-2-3);(-1-5)\\\\AC=(-1;-5;-6)

vetor bc = C-B
BC=(-3;-2;-1)-(4;6;-6)\\\\BC=(-3-4);(-2-6);(-1-(-6))\\\\BC=(-7;-8;5)


V=2ab-6ac-3bc

2ab=2*(6;3;-11)\\\\2ab=(12;6;-22)


6ac=6*(-1;-5;-6)\\\\6ac=(-6;-30;-36)


3bc=3*(-7;-8;5)\\\\3bc=(-21;-24;15)

agora temos

V=(12;6;-22) - (-6;-30;-36) - (-21;-24;15)\\\\V=(12;6;-22)+(6;30;36)+(21;24;-15)

fazendo a primeira soma 
(12;6;-22)+(6;30;36)\\\\(12+6) ; (6+30);(-22+36)\\\\(18;36;14)

restou 
V=(18;36;14)+(21;24;-15)\\\\V=(18+21);(36+24);(14-15)\\\\V=(39;60;-1)